The Role of Mediator of Cognitive Emotion Regulation Strategies in the Relationship Between Mindfulness and Perceived Stress in People with High Blood Pressure - Farahani, Samaneh; Rafiepoor, Amin; Jafari, Tayebeh (International Journal of Applied Behavioral Sciences, 2019)
Introduction: High blood pressure is one of the chronic medical conditions in the general population. The aim of this study was to investigate the mediating role of cognitive emotion regulation strategies in the relationship between mindfulness and perceived stress in patients with high blood pressure.Methods: A total of 216 high blood pressure patients who referred to medical centers in Tehran in 2018 were selected by available sampling method and participated in this study. Participants in the study completed The Perceived Stress Scale (PSS), the Cognitive Emotion Regulation Questionnaire (CERQ), and The Five Facets Mindfulness Questionnaire (FFMQ). For data analysis, Pearson correlation and path analysis were used. AMOS 22.0 was used to examine the fitness of the proposed model and path analysis.Results: The results of this study showed that there is a significant negative correlation between the adaptive cognitive emotion regulation strategies and mindfulness with perceived stress and positive correlation between the maladaptive cognitive emotion regulation strategies with perceived stress (P <0.01). The results of path analysis indicated that the indirect effect of mindfulness on perceived stress was statistically significant through adaptive cognitive emotion regulation strategies (0.09) and maladaptive cognitive-emotional regulation strategies (0.11), respectively (p <0.01).Conclusion: Based on the findings of this study, it can be concluded that the variables of mindfulness and adaptive cognitive-emotion regulation strategies contribute to the reduction of stress in people with hypertension, which in turn leads to prevention and control of blood pressure. It is necessary to consider these factors in health-related interventions related to blood pressure control.